Investigation of Coagulation Biomarkers to Assess Clinical Deterioration in SARS-CoV-2 Infection - Billoir, Paul; Alexandre, Kevin; Duflot, Thomas; Roger, Maxime; Miranda, Sébastien; Goria, Odile; Joly, Luc Marie; Demeyere, Mathieu; Feugray, Guillaume; Brunel, Valery; Etienne, Manuel; Le Cam Duchez, Véronique (Frontiers in Medicine, 2021)
Since December 2019, a pandemic caused by a new coronavirus has spread to more than 170 countries around the world. Worsening infected patients requiring intensive care unit (ICU) admission, associated with 30% of mortality. A part of worsening is induced by haemostasis deregulation. The aim of this study was to investigate the association of coagulation activation in COVID-19 progression. Thirty-five of the 99 patients got clinically worse. Final model of the logistic regression analysis revealed that O2 requirement (RR=7.27 [1.50-19.31]), monocytes below 0.2G/L (RR=2.88 [1.67-3.19]), fibrinogen levels (RR=1.45 [1.17-1.82] per g/L increase), prothrombin fragments 1+2 higher than 290 pM (RR=2.39 [1.20-3.30]) and thrombin peak (RR=1.28 [1.03-1.59] per 50 nM increase), were associated with an increased risk of clinical worsening. Fibrinogen level threshold of 5.5 g/L, thrombin peak measurement threshold of 99 pM and O2 requirement associated with clinical outcome in near than 80% of our cohort. In conclusion, we identified fibrinogen and thrombin peak at admission as coagulation biomarkers associated with an increase risk of intensive care unit admission or death. This finding allows initiating steroids and triage for worsening patients. Our results should therefore be considered as exploratory and deserve confirmation.